Espejos : una historia casi universal - Galeano, Eduardo, 1940-2015 (Madrid : Siglo Veintiuno de España Editores, S.A. ; México, D.F. : Siglo XXI Editores, S.A. de C.V. ; Buenos Aires : Siglo XXI Iberoamericana, S.A. : Siglo XXI Editores, S.A., 2008)
The unofficial history of the world seen--and mirrored to us--through the eyes and voices of history's unseen, unheard, and forgotten, over 5000 years of history.
Includes indexes.
Online resource; title from PDF title page (Digitalia, viewed July 8, 2015)
Keywords: History -- Miscellanea; Electronic books